Latihan Fisik & Sekresi PGC-1α Pada Obesitas - Arya Dwi Prastickho; Desiana Merawati; Sugiharto Sugiharto (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
Peroxisome proliferator activates gamma coactivator 1α (PGC-1α) receptors associated with oxidizing activity in adipose tissue and muscle, which is the prevention of increased obesity through non-pharmacological therapy. Physical exercise is believed to be a trigger for PGC-1α secretion as a strategy to prevent an increase in the prevalence of obesity and prevent the occurrence of metabolic syndrome. Physical exercise also improves metabolic health in obese individuals. Physical exercise is also believed to increase PGC-1α levels in obese individuals. after exercise, the thermogenic gene is expected to remain active. These conditions are favorable and attractive for the browning process to maintain homeostasis in response to a decrease in the AMP/ATP ratio and increased biogenesis in mitochondria. The decrease in AMP/ATP led to active AMPK, the ratio observed 3 hours after exercise. AMPK activation triggers activation of the PGC-1α gene receptor stimulating an increase in FNDC-5, which then cleaves into circulating irisin to activate UCP-1. Consequently, PGC-1α-induced UCP-1 activation enhances browning. The method of this article is to look at several journal articles and compare one journal with another, in the sense that the results of the analysis of research journals are combined based on their similarities and differences to draw new conclusions. According to previous studies, it was also shown that moderate and high-intensity exercise was proven to increase PGC-1α levels in obese individuals, both acutely and chronically.